People and settlements in Andalusian national parks. Residential development and quality of life as a trigger of naturbanization processes - Carolina del Valle Ramos; Maria José Prados Velasco (Investigaciones Geográficas)
Naturbanization processes explain how the presence of a protected space stimulates the processes of urbanization in surroundings areas. This paper investigates the perceptions and motivations of new and old residents using qualitative methodologies. Its aim is to explore the relationships between residential attraction and the preservation of environmental values. This research analyses, in a comparative way, the results of a survey of people living in municipalities surrounding the Doñana and Sierra Nevada national parks in Andalusia (southern Spain). The results reveal differences in residential aspects, environment, and landscape near these national parks. These prove the importance of the educational and economic level of respondents together with their residential history.